Gendered Scientization of Environmental Degradation: Countering Gender Stereotype of Village Women in Lakardowo, Indonesia - Azmi, Aulia Izzah; Lutfiah, Vita (CV. Literasi Indonesia, 2024)
This research aims to explore the gender dimensions of the use of science by the women's movement to respond to environmental injustice in Indonesia. Previous studies have explored the vulnerability of village women to environmental degradation due to their multiple roles as domestic workers, farmers, and nurturers. It indicated the weak position of women affected by environmental conflict. However, the concept of gendered scientization highlights how the turn to science in dealing with environmental threats might result in gendered opportunities and challenges in collective mobilization by citizens. To deeply analyze and categorize the result, the method used in this study is thematic analysis. The data collection techniques used were in-depth interviews, focus group discussions (FGDs), and documentation of secondary data related to the study. The results show that women in the Lakardowo Village are driven by feminine urges and generational concerns to protect the environment to mobilize an ecological movement to protect their land. Others found it important to arm themselves with science when the broader social discourse portrayed contamination concerns as stereotyping women as overreacting due to their scientific illiteracy.